Acute Mastoiditis with Facial Nerve Paralysis in Acute Myeloid Leukemia - Acharya, R; Tulachan, B (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 13-14 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6796